EL CONVENTO DE CARMELITAS CALZADOS DE MURCIA - Hernández Albadalejo, Elías; de la Peña Velasco, Concepción (Imafronte, 1993)
The monastery of Carmelites of Murcia. settled down in the old quorter of San Benito (presently del Carmen), was a 16th. century foundation with the City Council protection. This papel refers to the problems concerning the building of the monaster, in particular its cloister and church. The construction of this new church during the 18th. century the richest and most interesting stage of Murcian Baroque-coincided with a general process of urban reordenation at this zone, the riqht riverside of the River Segura.